Meaningful Learning in Primary Education: Implementation of Deep Learning Approach in Realizing the UNESCO Education Pillar at Madrasah Ibtidaiyah - Mustagfiroh, Siti Hikmatul; Mustaqim, Muhamad; Arifin, Nur (Dinamika Ilmu, 2025)
This research aims to explore the implementation of deep learning as a pedagogical approach in supporting meaningful learning and realizing the four pillars of UNESCO education in the context of Madrasah Ibtidaiyah. Using a case study design at Madrasah Ibtidaiyah in Kudus, this study focuses attention on the integration of meaningful and fun learning principles in classroom learning practices. The data uses interviews, observation and documentation analysis, as well as researchers as the main instruments. The findings in this study show that the deep learning approach is able to encourage active, critical, and reflective student engagement, where learning activities are closely connected to real experiences. This practice contributes significantly to the holistic formation of students' character, particularly within the framework of UNESCO's four pillars: learning do know. Learning to do, learning to be and learning to live together. However, this study also revealed a number of challenges, such as limited teacher readiness, inadequate learning facilities, and the need for continuous professional training to support effective implementation. This research provides valuable insights for educators and policymakers in designing inclusive, transformative, and contextual learning environments in Islamic-based basic education.